Compact empty substrate integrated waveguide with high performance and its application in microwave. Issue 11 (21st April 2021) - Qiang, Jingxia; Xu, Feng; Yang, Ling; Zhan, Junlin
Abstract: A compact slow‐wave empty substrate integrated waveguide (SW‐ESIW) structure is proposed in this article. This structure is composed of an empty substrate with a bottom layer including several rows of internal metallised via holes. In order to decrease both the lateral and longitudinal dimensions, the slow wave effect, caused by physical separation of electric and magnetic fields, is introduced while retaining the advantages of ESIW, such as high quality factor, small insertion loss, and the advantages of SIW, such as low cost and easy processing. Compared to the classical ESIW, the proposed SW‐ESIW structure achieves a size reduction of 37% and retains the triple‐layer structure. At the same time, in contrast with general SW‐SIW structure, which needs double layer with dielectric material, the novel waveguide obtains a significant performance improvement in insertion loss and quality factor. In the article, a fourth‐order filter is designed to verify the idea that the SW‐ESIW technology provides the low loss, high quality factor and compact structure. By combining the advantages of SW‐SIW and ESIW technology, the proposed SW‐ESIW structure can be widely applied to the microwave integrated circuits with miniaturisation and high quality factor.